Manipulating the cGAS-STING Axis: advancing innovative strategies for osteosarcoma therapeutics - Li, BingBing; Zhang, Cheng; Xu, XiaoJuan; Shen, QiQin; Luo, ShuNan; Hu, JunFeng (Frontiers in Immunology, 2025)
This paper explored the novel approach of targeting the cyclic guanosine monophosphate (GMP)-adenosine monophosphate (AMP) synthase-stimulator of interferon genes (cGAS-STING) pathway for the treatment of osteosarcoma (OS). Osteosarcoma is a common malignancy in adolescents. Most patients die from lung metastasis. It reviewed the epidemiology and pathological characteristics of OS, highlighting its highly malignant nature and tendency for pulmonary metastasis, underscoring the importance of identifying new therapeutic targets. The cGAS-STING pathway was closely associated with the malignant biological behaviors of OS cells, suggesting that targeting this pathway could be a promising therapeutic strategy. Currently, research on the role of the cGAS-STING pathway in OS treatment has been limited, and the underlying mechanisms remain unclear. Therefore, further investigation into the mechanisms of the cGAS-STING pathway in OS and the exploration of therapeutic strategies based on this pathway are of great significance for developing more effective treatments for OS. This paper offered a fresh perspective on the treatment of OS, providing hope for new therapeutic options for OS patients by targeting the cGAS-STING pathway.